2019
DOI: 10.1016/j.cyto.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Could the inhibition of IL-17 or IL-18 be a potential therapeutic opportunity for gastric cancer?

Abstract: Chronic inflammation is recognized as a key tumor-promoting factor in a number of epithelial cancers, including gastric cancer (GC). The production of pro-inflammatory cytokines in the tumor microenvironment by both the innate and the adaptive immune response can activate signaling pathways that are associated with increased cell survival and proliferation of cancer cells. Among the cytokines that have most commonly been linked to inflammation-associated cancers, are the Th17 cell-associated cytokines IL-17A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 157 publications
0
16
0
Order By: Relevance
“…26 Chronic inflammatory response can damage gastric mucosa and induce the formation of gastric cancer. 27 Various inflammatory factors secreted by inflammatory cells promote the occurrence and metastasis of tumors in different ways, so inhibiting inflammatory response is one of the key links in the prevention and treatment of gastric cancer. IL-17 is a pro-inflammatory cytokine that stimulates the NF-κB signaling pathway for the transcription of downstream effectors and promotes cell proliferation and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…26 Chronic inflammatory response can damage gastric mucosa and induce the formation of gastric cancer. 27 Various inflammatory factors secreted by inflammatory cells promote the occurrence and metastasis of tumors in different ways, so inhibiting inflammatory response is one of the key links in the prevention and treatment of gastric cancer. IL-17 is a pro-inflammatory cytokine that stimulates the NF-κB signaling pathway for the transcription of downstream effectors and promotes cell proliferation and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously demonstrated that both IL-33 and ST2 are highly expressed in tumor-associated microvessels, implying autocrine stimulation of angiogenesis during the progression of CRC ( 19 ). Cytokine signaling can be easily targeted pharmacologically ( 89 ), and several studies have examined the inhibitory efficacy of IL-33 or ST2 signals in murine CRC models. However, cytokine networks in tumors are very complex; one cytokine may have a wide range of biological effects, while different cytokines may possess the same function ( 38 ).…”
Section: Could Il-33 Be a Potential Biomarker And New Therapeutic Tarmentioning
confidence: 99%
“…In PDAC clinical trials, pegilodecakin is able to increase the activation of cytotoxic T cells and improve overall survival when combined with FOLFOX [82]. Further assessments of interleukins in cancer therapy are largely occurring at the preclinical level, with promising findings for targets such as IL-25 [73,80] as previously discussed. Fortunately, the prior interest in these and related targets for psoriasis, asthma, and inflammation-related disorders has resulted in a variety of existing therapies [83], including mABs with known human safety profiles that could be repurposed for cancer immunotherapy.…”
Section: Emerging Clinical Importance Of the Tmementioning
confidence: 94%
“…Indeed, ongoing clinical trials are demonstrating promise for these immunotherapeutic agents with or without combination therapy, and the success of PD-1/PD-L1 axis therapies has invigorated the pursuit of targets exploiting other immune-tumor interactions [76]. Prominent emerging targets in this field of development include CD47 [77], CD40 [78,79], interleukins such as IL-10 and IL-17 [73,80], inflammatory mediator IDO1 [81], and a variety of engineered viral, vaccine, and cell therapies.…”
Section: Emerging Clinical Importance Of the Tmementioning
confidence: 99%